X-RAY SINGLE-CRYSTAL STUDY OF SPINELS: IN SITU HEATING - Carbonin S.; Martignago F.; Menegazzo G.; Dal Negro A. (My University, 2002)
Two MgAl2O4 stoichiometric spinel crystals, one natural and one synthetic, were heated from 25 to 950 °C and studied in situ by single-crystal X-ray diffraction. The natural crystal, quenched from 850 °C, was further heated and cooled. Thermal expansion was characterized, and cation partitioning at the various temperatures was determined according to a model purposely constructed for high-temperature bond lengths. It was found that the structural evolution of the samples with temperature depended on order–disorder at room temperature. At the temperatures lower than the beginning of cation exchange, thermal expansion was completely reversible and the oxygen coordinate remained stable in spite of varying temperatures. At the temperature at which cation exchange starts, the disordered samples first tend to order and then to disorder at higher temperatures, at variance with the ordered sample, which tends to disorder steadily. In general, the evolution of the spinel structural state on cooling and heating over the same temperature range and the same time intervals does not follow the same path. In particular, in the 600–950 °C range, only partially reversible order–disorder processes occurred in the time span used for the experiments.